(untitled) (Praxis Educativa, 2024)
This article socializes some ongoing research at the intersection of three projects4 concerned with secondary education from a socio-critical perspective. It particularly deals with the High School Professional Program, which has been implemented since 2023 to secure the right to finish this educational level by means of recovering students who have abandoned or failed their courses and designing a flexible pedagogical model. In the framework of qualitative research, document analysis, participant observations, and an interview with one of the leading figures of the Program have yielded interesting results. Thus, some theses can be presented in these initial phase of fieldwork, as well as a few concerns about educational transformation in this postpandemic scenarios– a must to guarantee access to a dignified life.